Health-Related Quality of Life, Treatment Satisfaction, Adherence and Persistence in β-Thalassemia and Myelodysplastic Syndrome Patients with Iron Overload Receiving Deferasirox: Results from the EPIC Clinical Trial. (12th August 2012) - Porter, John; Bowden, Donald K.; Economou, Marina; Troncy, Jacques; Ganser, Arnold; Habr, Dany; Martin, Nicolas; Gater, Adam; Rofail, Diana; Abetz-Webb, Linda; Lau, Helen; Cappellini, Maria Domenica
Abstract : Treatment of iron overload using deferoxamine (DFO) is associated with significant deficits in patients' health-related quality of life (HRQOL) and low treatment satisfaction. The current article presents patient-reported HRQOL, satisfaction, adherence, and persistence data from β -thalassemia (n = 274 ) and myelodysplastic syndrome (MDS) patients (n = 168 ) patients participating in the Evaluation of Patients' Iron Chelation with Exjade (EPIC) study (NCT00171821); a large-scale 1-year, phase IIIb study investigating the efficacy and safety of the once-daily oral iron chelator, deferasirox. HRQOL and satisfaction, adherence, and persistence to iron chelation therapy (ICT) data were collected at baseline and end of study using the Medical Outcomes Short-Form 36-item Health Survey (SF-36v2) and the Satisfaction with ICT Questionnaire (SICT). Compared to age-matched norms, β -thalassemia and MDS patients reported lower SF-36 domain scores at baseline. Low levels of treatment satisfaction, adherence, and persistence were also observed. HRQOL improved following treatment with deferasirox, particularly among β -thalassemia patients. Furthermore, patients reported high levels of satisfaction with deferasirox at end of study and greater ICT adherence, and persistence. Findings suggest deferasirox improves HRQOL, treatment satisfaction, adherence, and persistence with ICT in β -thalassemia and MDS patients. Improving such outcomes is an important long-term goal for patients with iron overload.